Multiperiod Heat Exchanger Network Synthesis With Pinch-Based Strategies and Metaheuristics - Pavão, Leandro V.; Costa, Caliane B. B.; Ravagnani, Mauro A. S. S. (Frontiers in Sustainability, 2022)
Heat exchanger networks (HEN) are a widely studied subject. These systems may undergo important variations in their operating conditions. Such uncertainties lead networks to require some degree of flexibility. An efficient approach to address such uncertainties is the development of multiperiod solutions. However, these are difficult to develop since one must synthesize a network that is simultaneously feasible under a given number of conditions. The present work presents a method based on pinch insights and a hybrid meta-heuristic. It employs the “spaghetti” network concept as initial estimations for single-period networks, which are refined and merged in a single solution that is able to operate under multiple period conditions. The merged solution is refined as well with a multiperiod HEN model, and a final multiperiod network is achieved. The method was able to outperform previous literature regarding total annual costs (TAC) for the multiperiod HEN developed. The case study approached is one of the largest multiperiod cases for HEN synthesis in the literature (15 streams, 4 periods). The obtained solution has TAC 3.5% lower than literature solutions.